HOLDING TIME INFLUENCES FROZEN SEMEN QUALITY OF MIZO LOCAL BOAR (ZOVAWK) - DAS, AK; LALRINTLUANGA, K; AHMED, FA; AHMED, N; ALI, MA; SUBUDHI, PK; DEURI, D (The Indian Journal of Animal Reproduction, 2016)
Twenty ejaculates from three boars were used to establish the impact of three holding time (1h, 3h, 5h) on the quality of frozen semen. Sperm motility, live sperm, HOST-reacted sperm and sperms with intact acrosome at equilibration and during post-thaw period were higher (p
Keywords: Cryopreservation; Boar; Frozen semen; Holding time; Sperm parameters